PEMBERIAN LIMBAH PERKEBUNAN SINGKONG YANG DISUPLEMENTASI SENG DAN KOBALT TERHADAP PERFORMA REPRODUKSI DOMBA BETINA (Utilization of Cassava Plantation Waste Supplemented with Zinc and Cobalton Reproduction Performance of Ewe) - Hernaman, Iman; Hidajat, Kundrat; Budiman, Atun; Nurachma, Siti (Jurnal Kedokteran Hewan, 2016)
The study aimed to evaluate the utilization of cassava plantation waste suplemented with zinc and cobalt on ewe reproduction performance. Six pregnacy ewes were allocated at experimentrations, i.e. K1: control (50% fresh grass + 50% concentrate) and K2: 50% fresh grass + 50% cassava plantation waste + 30 ppm zinc + 5 ppm cobalt. The results showed that the concentration of zinc and cobalt in blood of ewe in group K1 and K1 were 7.03 vs 8.22 ppm and 0.48 vs 0.44 ppm, respectively, while in faeces were 147,72 vs 158.59 ppm and 8.3 vs 9.8 ppm. In addition, the concentration of alkaline phosphatase and progresterone in blood were 116 vs 196 u/l and 0.56 vs 0.59 mg/ml, respectively. The average of offsprings weight on 24 day postpartum in K1 and K2 was 3.48 vs 3.16kg. In conclusion, cassava plantation waste could be used as feed for pregnancy and lactating ewe. Supplementation of 30 ppm zinc is efectively increase the concentration of zinc and alkaline phosphatase in blood.Key words: cobalt, reproduction, cassava, zinc, ewe